Preparing the leg for ground contact in running: the contribution of feed-forward and visual feedback - Müller, R.; Häufle, D. F. B.; Blickhan, R. (The Journal of Experimental Biology, 2015)
While running on uneven ground, humans are able to negotiate visible but also camouflaged changes in ground level. Previous studies have shown that the leg kinematics before touch down change with ground level. The present study experimentally investigated the contributions of visual perception (visual feedback), proprioceptive feedback and feed-forward patterns to the muscle activity responsible for these adaptations. The activity of three bilateral lower limb muscles (m. gastrocnemius medialis, m. tibialis anterior and m. vastus medialis) of nine healthy subjects was recorded during running across visible (drop of 0, -5 and -10 cm) and camouflaged changes in ground level (drop of 0 and -10 cm). The results reveal that at touchdown with longer flight time, m. tibialis anterior activation decreases and m. vastus medialis activation increases purely by feed-forward driven (flight time-dependent) muscle activation patterns, while m. gastrocnemius medialis activation increase is additionally influenced by visual feedback. Thus, feed-forward driven muscle activation patterns are sufficient to explain the experimentally observed adjustments of the leg at touchdown.